TEST THE ABILITY OF SEDIMENT BACTERIA ISOLATES IN DEGRADATING PHENOL - Monika, Siska; Yoswaty, Dessy; Nursyirwani, Nursyirwani (Asian Journal of Aquatic Sciences, 2019)
Phenol degrading bacteria can be found in various habitats in marine environments. This study aims to obtain bacteria from sediments that are able to degrade phenol. The process of bacterial purification and degradation was carried out from August to September 2018 at the Marine Microbiology Laboratory, Department of Marine Sciences, Faculty of Fisheries and Marine, University of Riau. Analysis of the reduction in phenol concentration was carried out using the APHA 5530 method using UV-VIS spectrophotometry conducted at the Health and Environment Laboratory. The bacterial isolates used as test bacteria were isolates BF1A, BF4B and BF9C. Bacterial and biochemical tests were carried out for all bacterial isolates. Two isolated showed mehyl red negative, all isolates were motile. Three isolates were positive catalase, able to ferment glucose and sucrose fermented citrate and two isolat were Gram negative bacterial. The three bacterial isolates were able to degrade phenol with the highest degradation for 1ppm shown in isolates BF1A, the highest degradation of concentrations of 2 ppm and 3 ppm was shown in isolates BF9C. Thus, the isolat BF9C was able to degrade the highest phenol